FACTORS AFFECT CLEAN WATER PRODUCTION PERFORMANCE : A REVIEW ON ULTRAFILTRATION MEMBRANE - M. Shahidul, Islam; Michael, A. B. (Science International, 2022)
: This study aims to reveal factors that affect the performance of Ultrafilter membranes (UFM) in producing clean water. This study was designed to unlock the influence of feedwater quality, feedwater pre-treatment efficiency, energy consumption rate of UFM, and operating costs in producing clean water. Nearly a hundred journal articles related to the performance of UFM, published from 2000 to 2022, were reviewed. The outcome of the review revealed that factors such as feedwater pre-treatment, higher feedwater pressure, chemically enhanced backwash, and osmotic pressure are positively associated with the performance of the UFM. Additionally, feedwater quality such as low pH, TSS, turbidity, and COD are the sources of cake layer that affect energy consumption and operating cost in producing clean water by the UFM. This study concludes that UFM is an effective water treatment technology but its performance depends on feedwater quality and mode plant operations. This study also suggests further research on the UFM to discover optimum operating conditions to optimize the energy consumption rate and water production cost for contributing to achieving sustainable development goal 6(SDG 6).